PENGARUH INDEPENDENSI, KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, PENGALAMAN, DAN SKEPTISME PROFESIONAL TERHADAP PENGAMBILAN KEPUTUSAN BAGI AUDITOR UNTUK MELAKUKAN OPINI AUDIT (Studi Empiris Pada BPK RI Perwakilan Provinsi Jawa Tengah) - Siti Anisa, 12.05.52.0041; Himawan, Arief (Students' Journal of Accounting and Banking, 2016)
This study examines the effect of independence, intellectual, and spiritual intelligence, experience, and professional skepticism towards decision making for the auditorto perform the audit opinion. This research is done in a auditing firm Central Java. Data used in this study are primary data. The data in this study were obtained directly from the auditors who worked at auditing firm Central Java as many as 58 samples by purposive sampling using multiple linear regression techniques. The results showed that the independence, intellectual, spiritual intelligence, experience, and positive professional skepticsm had significant impact on decision making for the auditor to perform the audit opinion.Keywords: Independence, Intellectual, Emotional, Spiritual Intelligence, Experience, Professional Skepticsm